(untitled) (Journal of Health Sciences, 2014)
Introduction Pap smear, the main tool of cervical cancer screening is not always available, but some patients are in urgent need for proper diagnostic. Aim of this article was to investigate accuracy of colposcopy for detection of squamous intraepithelial lesions of low or high grade (LGSIL, HGSIL) and to promote colposcopy as useful tool for detection of patients in need for immediate further diagnostics. Methods Prospective multicentric study performed in B&H in 2012 -2013 included 87 patients with colposcopic images related to squamous intraepithelial lesion (SIL) who formed experimental group: 56 patients with colposcopic images related to LGSIL and 31 patients related to HGSIL. Control group included 50 patients without colposcopic abnormalities. To test accuracy of colposcopy, PAP smear and histology were used. For statistical analysis χ2 was used.Results 94.5% patients in experimental group had abnormal PAP test: 64.3% correlated to LGSIL (χ2= 60.48 P < 0.0001), while 64.5% correlated to HGSIL (χ2 = 54.23 P<0.0001) Odds Ratio = 490; 95% CI = 42.024 to 5713.304). HGSIL was confirmed in 27 (87%) cases by histology (CIN II /CIN III). There were no statistically significant differences between colposcopic finding and histology results (Yates-corrected χ2 = 0.33 P = .5637)Conclusions This study showed high level of correlation between colposcopy and PAP results (63-64%) and to histology for HGSIL (87%). In absence of PAP test colposcopy could be used to select patients in need for biopsy.